Use of Left Gastric Vein as an Alternative for Portal Flow Reconstruction in Liver Transplantation - Uirá Fernandes Teixeira; Mayara Christ Machry; Marcos Bertozzi Goldoni; Cristine Kruse; João Alfredo Diedrich; Pablo Duarte Rodrigues; Caroline Becker Giacomazzi; Estéfano Aurélio Negri; Matheus Koop; Carlos Gustavo Spode Gomes; José Artur Sampaio; Paulo Roberto Ott Fontes; et al. (Case Reports in Surgery)
Portal vein thrombosis is observed in up to 10% of liver transplant candidates, hindering execution of the procedure. A dilated gastric vein is an alternative to portal vein reconstruction and decompression of splanchnic bed. We present two cases of patients with portal cavernoma and dilated left gastric vein draining splanchnic bed who underwent liver transplantation. The vein was dissected and sectioned near the cardia; the proximal segment was ligated with suture and the distal segment was anastomosed to the donor portal vein. Gastroportal anastomosis is an excellent option for portal reconstruction in the presence of thrombosis or hypoplasia. It allows an adequate splanchnic drainage and direction of hepatotrophic factors to the graft.